Knowledge Representation and Utilisation in a Man-Machine Dialogue with a Medical Decision Aid System - Joubert, M.; Fieschi, M.; Fieschi, D.; Roux, M. (Methods of Information in Medicine, 1982)
This study presents the man-machine communication procedure, called MEDIUM, with the medical decision aid system SPHINX. The knowledge processed by this procedure is concerned with the entities of the medical discourse, that is the signs, the symptoms and the results of clinical and paraclinical examinations. At first level, the knowledge is constituted by the definitions of the entities and their specific properties. At a second level, the knowledge is constituted by logical formulas which translate the relations that link entities. Part of the coherence of the discourse is judged with regard to the definitions of the entities. The coherence is completely established by evaluating the truth values of the formulas according to the data already stored during the session. Parts of sessions with the procedure MEDIUM are presented and results are discussed.
Keywords: Medical Man-Machine Dialogue; Knowledge Representation; Expert System; Artificial Intelligence